A Survey on Malicious Access Point Detection Methods for Wireless Local Area Network - Patil, Sandip; Vanjale, Sandeep (International Journal of Computer Sciences and Engineering, 2014)
Wireless access points are today popularly used for the convenience of mobile users. The growing acceptance of wireless local area networks (WLAN) presented different risks of wireless security attacks. Now a day's in many public places like bus stations, restaurant, malls etc. provides Wi-Fi connectivity to the users with free of cost. These public places having a device like wireless access point through which they provide service to the end users. The growing acceptance of wireless local area network causes a risk of wireless security attacks. The attacker creates a malicious access point to attract the users and perform attacks on user devices through WLAN. Malicious access point is one of the serious threats in wireless local area network. In this paper we have presented survey on recent different malicious access point detection solutions. We identified and compared their advantages and weaknesses.